Ciceros Kritik an dem antonischen Provokationsgesetz - Kuznetsova, Natalia (Hyperboreus, 2021)
Cic. Phil. I, 21–23 is the only source for the Antonian bill of 43 BC, which may have allowed the appeal to the people (provocatio) against the condemnation de vi et maiestatis by the jury courts. This bill is practically the only law on the appeal which dates to a relatively well-attested period and oﬀers contemporary evidence. This sounds like a good chance to answer at least some of the many questions concerning the right of appeal to the people. The paper aims at two points: (1) what procedure for the appeal is attested by the Philippic?; (2) was the appeal against any court allowed or at least considerable before the Antonian bill?Unfortunately, Cicero does not give any reliable information concerning both questions. There were attempts to base some hypotheses on his criticism of the Antonian bill, but no arguments set out for their support turn out to be convincing. Hence the answers to both questions are to be based on other evidence concerning provocatio. Much depends on the texts which allow diﬀerent interpretations and require careful explanation, but as far as can be said at present, (1) the provocatio may normally have led to a comitial court; (2) before the Antonian bill the appeal may have been appropriate only in case of an out-of-court punishment, and the reform Antonius proposed may have been unprecedented.